2014
DOI: 10.17795/ijep15610
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis Risk Factors in the Southwestern Province of Khuzestan, Iran

Abstract: Background: Brucellosis is an endemic infectious disease in Iran. Prevention strategies are based upon identification of risk factors for brucellosis. Objectives: The purpose of this study was to determine the principal risk factors for brucellosis in Khuzestan Province, Southwestern Iran. Patients and Methods: In this retrospective study, the medical records of 162 admitted patients, 81 brucellosis cases and 81 controls with other unrelated conditions, were reviewed. The study was undertaken in the Razi Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Alavi et al (26) showed significant associations between the occurrence of brucellosis and factors such as exposure to animals and their waste and consumption of unpasteurized dairy products. According to the results of a study carried out by John et al (27) in Tanzanian rural, participation in livestock abortion was significantly associated with developing brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…Alavi et al (26) showed significant associations between the occurrence of brucellosis and factors such as exposure to animals and their waste and consumption of unpasteurized dairy products. According to the results of a study carried out by John et al (27) in Tanzanian rural, participation in livestock abortion was significantly associated with developing brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella melitensis is the most common cause of human disease. Sheep, goat and camel are the main sources of infection (Alavi, Mugahi, Nashibi, & Gharkholu, 2014). Annually, brucellosis causes more than 500,000 infections worldwide (Pappas, Papadimitriou, Akritidis, Christou, & Tsianos, 2006).…”
Section: Brucellosismentioning
confidence: 99%
“…In addition, brucellosis was mainly found in adult male patients aged 20–39 yr old (41%) which of them 67% were male. In a published report, brucellosis patients had 31.3 yr median age (16,19–21). About 2% of studied samples were positive for Brucella DNA using PCR method.…”
Section: Discussionmentioning
confidence: 99%